Effectiveness of Solution-Focused Group Counseling on the Mental Health of Midwifery Students - Javid, Nezhat; Ahmadi, Atefeh; Mirzaei, Moghadameh; Atghaei, Monavvareh (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective The present study was conducted with the objective of investigating the effectiveness of solution-focused group counseling (SFGC) on promoting the mental health of midwifery students.Methods The present study is an intervention-based study with a pretest, a post-test, and a control group. The statistical population included all of the midwifery students studying in the midwifery department of the Bam University of Medical Sciences, Kerman, Iran, who filled out the General Health Questionnaire (GHQ) in the screening phase. In the second phase, 40 individuals, having a low level of mental health based on the cutoff score of 23, were selected and randomly divided into 2 groups (intervention and control), each group with 20 participants. The intervention group participated in 5 sessions of 75 minutes for SFGC. Then, the post-test was held in both groups and the data analysis was conducted using the Mann-Whitney and the Kruskal-Wallis test with IBM SPSS Statistics for Windows, Version 21.0 (IBM Corp, Armonk, NY, USA). The significance level was considered as p < 0.05.Results The findings showed that the mean of the post-test mental health scores of the intervention group (14.5 ± 50.35) and of the control group (23.6 ± 35.83) showed a statistically significant difference (p < 0.0001). Moreover, the comparison between the mean scores of the mental health subscales (physical symptoms, stress, social performance, and depression) showed a statistically significant difference in these groups, and SFGC improved physical symptoms, stress, social performance, and depression in the members of the intervention group.Conclusion Solution-focused group counseling may improve all levels of mental health. This type of counseling is recommended to be used to solve the psychological problems and to improve the mental health of students, as well as of the staff of the health system.
Keywords: solution-focused group counseling; mental health; midwifery